Detection and Genetic Characterization of Atypical Porcine Pestivirus in Piglets With Congenital Tremors in Southern China - Xie, Yongsheng; Wang, Xiaoru; Su, Danping; Feng, Junsen; Wei, Liuming; Cai, Weiyou; Li, Jinhui; Lin, Shaorong; Yan, He; He, Dongsheng (Frontiers in Microbiology, 2019)
Atypical porcine pestivirus (APPV) is an RNA virus newly discovered from swine in Asia, Europe, and the Americas. This novel virus has been confirmed as the cause of congenital tremor (CT) in piglets, which causes tensive economic losses to the swine industry. To investigate the genetic diversity and evolutionary relationship of APPV in China, 83 piglet samples with severe CT clinical signs were obtained from 12 commercial swine farms in 3 provinces of Southern China. RT-PCR revealed that the positive rates of APPV were as high as 100% (12/12) for the swine farms and 90.4% (75/83) for the samples. Subsequently, a portion of the positive samples was selected for sequencing of the E2 gene and full-length genome. Phylogenetic analysis showed that 62.5% of the sequences belonged to a novel APPV clade designated genotype 3, which showed 81.0–82.1% sequence identity to genotypes 1 and 2. Amino acid sequence alignment showed that E2 protein of genotype 3 has three specific mutation sites, namely I19V, Y82F, and N107G. The results of the present study demonstrate that a novel APPV genotype, which is widely distributed in severe CT clinical samples in Southern China, was genetically diverse and was the predominant genotype. We advocate for the inclusion of genotype 3 during revision of the APPV typing method.